Screening and Profiling of Antioxidant Activity in Mud Crab (Scylla Serrata) from Banyuasin Waters - Rozirwan, Rozirwan; Lestari, Ning Intan; Winarta, Yoga; Isnaini, Isnaini; Putri, Wike Ayu Eka; Hendri, Muhammad; Ulqodry, Tengku Zia; Fauziyah, Fauziyah; Melki, Melki; Nugroho, Redho Yoga; Mohamed, Che Abd Rahim (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Mangrove crab (Scylla serrata) as one of the crustacean species, has a variety of bioactive compounds that can be utilized in the field of pharmacology. Antioxidant compounds act as therapeutic agents against degenerative diseases. Banyuasin waters have mangrove vegetation with associated marine organisms that have the potential to be studied for bioactive compounds. This study aims to identify the phytochemical profile quantitatively and qualitatively, samples were collected from mud flats near mangrove ecosystems in Banyuasin waters, South Sumatra. Samples were tested for antioxidant activity using the DPPH test, and IC50 values, qualitative phytochemical identification, and phytochemical profiles were calculated using Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Based on the results of antioxidant testing, the IC50 value of S. serrata extract is 2.25 ppm, the sample is included in the category of very strong antioxidants. Phytochemical test results showed that the compound is thought to contain antioxidant activity from flavonoids and triterpenoids. GC-MS analysis detected major compound groups of alkaloids, purines, and vitamins. Minor compound groups detected amines, terpenoids, monosaccharides, amino acids, fatty acids, silanes, formamides, heterocycles, carboxylic acids, aminoglycosides, naphthalene derivatives, nitriles, amides, glycosides, and peptides. S. serrata extract shows very strong antioxidant activity, with major compounds such as alkaloids, purines, and vitamins. S. serrata extract detected compounds that have been reported as anti-inflammatory, anticancer, antimicrobial, and antiviral. These findings highlight the pharmaceutical potential of S. serrata as a source of bioactive compounds. The results of this study provide valuable information for the development of alternative medicines derived from marine organisms.